Enhanced electrical and optoelectrical properties of cadmium selenide nanobelts by chlorine doping. (1st January 2014) - Zhang, Lijie; Yu, Hongfei; Cao, Wei; Zou, Chao; Dong, Youqing; Zhu, Da‐Ming; Huang, Shaoming
Abstract : Single‐crystalline chlorine‐doped cadmium selenide (CdSe) nanobelts (NBs) with a wurtzite structure were synthesised by using CdSe and InCl3 powder as sources via a co‐evaporation approach. The investigation of the performance of the field‐effect transistors fabricated from Cl‐doped NBs shows n ‐type conduction behaviour and enhanced conductivity (1–70 S/cm). Furthermore, it is found that the photoconductivity (illuminated by a white light with a power density of 1.3 mW/cm 2 ) increases with the enhancement of the conductivity. Photoconductive analysis reveals that the Cl‐doped NBs show excellent photoresponse properties, with responsivity of 8.87 × 10 5 AW −1 and a corresponding external quantum efficiency of 1.74 × 10 6 when illuminated under a 650 nm light and biased 1 V. In addition, the electrical properties of the Cl‐doped NBs can be influenced by changing the ambiance, which is caused by their surface states.